Quercetin induces lipid domain-dependent permeability - Leite, Natália Bueno [UNESP]; Martins, Danubia Batista [UNESP]; Alvares, Dayane S. [UNESP]; Cabrera, Marcia Perez dos Santos [UNESP] (Elsevier, 2022)
Quercetin is a polyphenolic molecule with a broad spectrum of biological activities derived from its antioxidant property. Its mechanism of action has been explained by its binding and/or interference with enzymes, receptors, transporters and signal transduction systems. Since these important mechanisms generally occur in membrane environments, within and through lipid bilayers, investigating the biophysical properties related to the diversity of lipid compositions of cell membranes may be the key to understanding the role of cell membrane in these processes. In this work, we explored the interaction of quercetin with model membranes of different lipid compositions to access the importance of lipid phases and bilayer homogeneity to the action of quercetin and contribute to the understanding of quercetin multiple activities. Analysis of the influence of quercetin on the morphology and permeability of GUVs, the rigidity of LUVs and affinity to these vesicles showed that quercetin strongly partitions to the more homogeneous environments, but significantly permeates and modifies the more heterogeneous where liquid-disordered, liquid-ordered and solid phases coexist. Our findings support the condensing effect of quercetin, which is observed through a significant rigidifying of bilayers containing 40% cholesterol, but much less evidenced when it is reduced to 20% or in its absence. Nevertheless, the presence of sphingomyelin in the ternary system led to a more heterogeneous bilayer with the formation of micrometric and probably also nanometric domains, which coalesce in the presence of quercetin. This observation together with increased permeability points to an insertion effect.
Keywords: Cholesterol; Giant vesicles microscopy; Lipid bilayer effects; Lipid/water partition coefficients; Phospholipid membranes; Quercetin